2015
DOI: 10.3899/jrheum.140370
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Is Common in Never-smoking Patients with Primary Sjögren Syndrome

Abstract: COPD was a common finding in patients with pSS, even among never-smoking patients. An obstructive pattern was the predominant PFT finding in patients with pSS, although a superimposed restrictive lung disease could not be excluded. The results suggest that the disease per se is involved in the development of COPD in pSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 25 publications
1
26
1
Order By: Relevance
“…Extraglandular manifestations affecting various organs including the lungs are common amongst pSS patients [39] and approximately 50% of pSS patients report dry cough [3]. However, involvement of the respiratory system in pSS entails not only dry airways, but also obstructive airway disease [8], including chronic obstructive pulmonary disease (COPD) [5, 6], as well as interstitial lung disease (ILD) [3, 4, 10], all of which can co-exist in the same patient. Furthermore, all types of respiratory involvement can result in respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraglandular manifestations affecting various organs including the lungs are common amongst pSS patients [39] and approximately 50% of pSS patients report dry cough [3]. However, involvement of the respiratory system in pSS entails not only dry airways, but also obstructive airway disease [8], including chronic obstructive pulmonary disease (COPD) [5, 6], as well as interstitial lung disease (ILD) [3, 4, 10], all of which can co-exist in the same patient. Furthermore, all types of respiratory involvement can result in respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although pulmonary involvement seems to be subclinical in a substantial fraction of pSS patients [4], concomitant pulmonary involvement in pSS has been shown to be associated with a fourfold increased risk of mortality after 10 years of disease [7]. It has previously been shown that COPD is a common finding in pSS patients, even among never-smoking patients [5, 6]. To the best of our knowledge, no previous study has investigated to what degree COPD contributes to the respiratory symptoms in pSS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Primary Sjögren's syndrome (pSS) is a progressive systemic disease, characterized by autoimmune lymphocytic infiltration of exocrine glands and sicca symptoms. Various respiratory symptoms are also commonly encountered in pSS patients (1)(2)(3)(4), and multiple nonexocrine organs, including the lungs and airways, have been described as being affected in the disease (2,3,(5)(6)(7). In addition, a high prevalence of chronic obstructive pulmonary disease (COPD) in pSS has been reported (8,9), even among never-smoking pSS patients (6), strongly indicating that the disease per se is involved in COPD development.…”
mentioning
confidence: 99%
“…Various respiratory symptoms are also commonly encountered in pSS patients (1)(2)(3)(4), and multiple nonexocrine organs, including the lungs and airways, have been described as being affected in the disease (2,3,(5)(6)(7). In addition, a high prevalence of chronic obstructive pulmonary disease (COPD) in pSS has been reported (8,9), even among never-smoking pSS patients (6), strongly indicating that the disease per se is involved in COPD development. Besides COPD and small airway disease (2)(3)(4), interstitial lung disease (4,10,11) and dry airways are also found in a substantial fraction of patients (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation